El gasto del sector educación y la pobreza en el departamento de Loreto periodo 2016 – 2020 - Salinas Ruiz, Rosa Karin (2022)
As is known, education is one of the pillars to escape poverty, which is why it is essential that countries have a good public education system. The purpose of the study is to link the expenses incurred by the Education sector and the existence of poor people in the area of Loreto in the study years 2016 - 2020. Taking into account what is specified, this thesis is prepared, approved as Quantitative - Correlational and with a Non-Experimental scheme. The corollary of the research is that Education sector spending does not show an association with poverty in the regional jurisdiction over the years. 2016 - 2020, truth supported by the figures of the Correlation Coefficient r = -0.2695642000; and the Coefficient of Determination R2 = 0.072664858; values that bring to light the statistical insignificance and influence of related variables. Likewise, the item that concentrates the largest expenditure in the Education sector is “Personal and Social Obligations” with an execution of S/. 1,733,350,846.40; equivalent to 83.23% of the total. In that same sense, the analyzed program referring to the achievements of basic studies students was the first destination of the billing, executing the sum of S/. 1,615,512,104.38; which represents 77.57% of the total. On the other way, departmental precariousness showed unpredictable behavior over time with an average of 33.72% per year.